Antagonistic effects of essential oils from selected Malaysian herbs and spices against spoilage and mycotoxigenic fungi on food packaging application - Ramli, Mazliza (2022)
Essential oils (EO) have a long history and wide application. Although EO of various herbs and spices from other parts of the world have shown antifungal effects, those from Malaysian herbs and spices remain underreported; thus, they can be further utilised in the search for novel bioactive compounds as natural antifungals to fulfil the consumers' demand for greener, safer, healthier, and higher‐quality foods with longer shelf life. Therefore, the objectives of the present work were (i) to investigate the fungicidal and fungistatic potentials of commercial EO from selected Malaysian herbs and spices against common spoilage and mycotoxigenic fungi; and (ii) to examine mycotoxin prevention and reduction in peanut through the incorporation of the most potent EO in food packaging system. Essential oils from ten herbs and spices (betel, cinnamon, clove, coriander, galangal, ginger, lemongrass, lime, nutmeg, turmeric) were analysed against five common foodborne spoilage and mycotoxigenic fungi; which were Aspergillus flavus, A. parasiticus, A. niger, Fusarium verticillioides, and F. incarnatum. Fungal isolates were obtained from common household food products (maize and peanuts), and isolated by the culture method. Molecular identification of the fungal isolates was performed using primer pair of the Internal Transcribed Spacer (ITS) region. The mycotoxigenic potential of fungal isolates was determined by high performance liquid chromatography with a fluorescence detector (HPLC-FLD). The EO bioactive compounds were identified by gas chromatography and mass spectrometry (GC-MS). Preliminary in vitro screening was conducted with the agar disk diffusion and agar well diffusion methods on Potato Dextrose Agar (PDA), and microwell assay method on Potato Dextrose Broth (PDB). Following this, three most potent EO were selected for their Minimal Inhibitory Concentration (MIC), Minimal Fungicidal Concentration (MFC), and fungal spore germination test. Molecular identification confirmed the fungal isolates’ identity with existing species in the GenBank. Based on HPLC-FLD results, all the fungal isolates were confirmed to be mycotoxigenic based on their ability to produce mycotoxins. Based on GC-MS results, a total of 120 bioactive compounds were detected from the EO; which were 26.25% anethole (betel), 63.39% cinnamaldehyde (cinnamon), 87.16% eugenol (clove), 54.79% linalool (coriander), 29.56% propenoic acid (galangal), 26.32% α-zingiberene (ginger), 42.61% geranial (lemongrass), 39.84% limonene (lime), 27.80% β-phellandrene (nutmeg), and 41.81% ar-turmerone (turmeric). Based on preliminary in vitro screening, cinnamon, clove, and lemongrass EO yielded the highest fungal growth inhibition. Further, cinnamon EO yielded the lowest MIC, MFC, and spore germination, hence were selected to be applied in food packaging system. The inhibitory effects of cinnamon EO were found comparable to the commercial antifungal, cycloheximide. Sachet including inclusion complexes (ICs; a combination of cinnamon EO and β- cyclodextrin) by kneading method was prepared, and the fungal growth inhibition in vitro was determined under different temperature (25°C, 50°C, and 75°C) and pH values (5.5, 7.4, and 13.0) to see its stability in peanut. The ICs’ antifungal activity in peanuts was also determined in terms of aflatoxin reduction (peanut was selected since it is the most commonly colonised food crop commodity by Aspergillus section Flavi). The prepared ICs showed excellent fungal growth inhibition in vitro and aflatoxin reduction in peanuts as compared to control sample. Various temperature levels and pH values did not affect the ICs’ activity.